2018
DOI: 10.1177/2050640618773517
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full‐thickness resection of duodenal lesions—a retrospective analysis of 20 FTRD cases

Abstract: This study confirmed the feasibility of duodenal EFTR and indicates good efficacy and safety. Larger studies are needed to further investigate this novel technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
66
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 16 publications
1
66
0
6
Order By: Relevance
“…EMR is associated with positive vertical margins, or a crush and burn effect on the resected specimen, which leads to difficulties in performing a precise pathological evaluation. Recently, endoscopic full-thickness resection (EFTR) with the full-thickness resection devise (FTRD; Ovesco Endoscopy, Tübingen, Germany) for duodenal tumors had been reported [31,32]. Bauder et al reported that complete resection rates were 80% in five subepithelial tumors treated by FTRD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EMR is associated with positive vertical margins, or a crush and burn effect on the resected specimen, which leads to difficulties in performing a precise pathological evaluation. Recently, endoscopic full-thickness resection (EFTR) with the full-thickness resection devise (FTRD; Ovesco Endoscopy, Tübingen, Germany) for duodenal tumors had been reported [31,32]. Bauder et al reported that complete resection rates were 80% in five subepithelial tumors treated by FTRD.…”
Section: Discussionmentioning
confidence: 99%
“…Bauder et al reported that complete resection rates were 80% in five subepithelial tumors treated by FTRD. Their results suggested that EFTR is effective for NAD-NET, but the evidence is insufficient because of the small sample size [32]. Therefore, at the moment, ESD is the preferred method for NAD-NET to ensure accurate pathological diagnosis and avoid additional surgical resection for residual tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first published case in which EFTR has been used in a recurrent perianastomotic cancer in the upper gastrointestinal tract [1]. Moreover, stent placement was effective in resolving stenosis when EFTR was complicated by lumen occlusion.…”
mentioning
confidence: 76%
“…A full-thickness resection device (FTRD; Ovesco Endoscopy ® ) enables endoscopic transmural resection of suitable lesions with a fast minimally invasive technique [2]. A colonic FTRD was used for duodenal lesions as an "off-label" indication with good clinical outcomes and a complication rate comparable to duodenal endoscopic mucosal resection [3]. A duodenal FTRD (d-FTRD) with smaller diameter (19.5 vs. 21 mm), balloonassisted insertion and less clip interdental space was developed allowing easier upper oesophageal sphincter passage and minimising bleeding risk.We describe a 74-year-old male with a 10-mm postpyloric bulbar submucosal lesion (Fig.…”
mentioning
confidence: 99%